(untitled) (World Bulletin of Public Health, 2024)
It is known that patients with cranial arch defects, under the influence of atmospheric pressure and other provoking factors, gradually develop the "trepanned skull" syndrome, which includes several components in the form of meteopathy, asthenia, psychopathy, limb paresis, aphasia and epileptic seizures. Epileptic seizures are one of the frequent elements of the "trepanned skull" syndrome. The focal component of these seizures has a topographic localization corresponding to the localization of the bone defect. It has been established that the main cause of the development of epileptic seizures in patients with cranial arch defects is the development of an aponeuroticmeningocerebral scar in the area of the postoperative defect, which is confirmed by the development of a positive clinical effect after the operation "excision of meningocerebral scars followed by cranioplasty."